Comparative evaluation of baseline cleanliness of food contact surfaces in fishery based microenterprise units by ATP-Bioluminescence and conventional microbiological methods - Hassan, F.; Nija, K. V.; Sankar, T. V. (Indian Journal of Fisheries, 2018)
The baseline cleanliness of food contact surfaces namely floor, working tables, workers’ hands, utensils and machinery of a fishery-based microenterprise were examined by traditional microbiological swab analysis method and ATP-bioluminescence method. The study showed that swab results, measured in relative light unit which is proportional to total recovered ATP, did not have significant correlation with standard method of microbiological swab in the adjacent sites of equal area. The study also examined the bactericidal efficiency of selected commercially available sanitisers and the effect of treatment was found to be significantly different from each other. Analysis of percentage reduction of bacterial load on food contact surfaces showed that commercially available stabilised hydrogen peroxide was more effective than sodium hypochlorite used in the food industries (p<0.05).